Pengaruh Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Studi Kasus di Kedai Belikopi Mojosongo) - Fadilla Budiardhani; Didik Setyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study determine the effect of price and service quality on purchasing decisions at Kedai Belikopi, Mojosongo Branch. The data used is primary data from answers to questionnaires given to customers of Kedai Belikopi Mojosongo Branch. This study uses a quantitative methodology. The research analysis used was multiple linear regression analysis of two independent variables and one dependent variable. The results showed that both service quality and price had a significant influence on purchasing decisions at the Kedai Belikopi, Mojosongo Branch.